Assessment of Antioxidants in Selected Plant Rootstocks - Magnus, Samuel; Gazdik, Filip; Anjum, Naser A; Kadlecova, Eliska; Lackova, Zuzana; Cernei, Natalia; Brtnicky, Martin; Kynicky, Jindrich; Klejdus, Borivoj; Necas, Tomas; Zitka, Ondrej (Antioxidants (Basel, Switzerland), 2020)
The service tree (Sorbus domestica) is a wild fruit tree with immense medicinal and industrial value. This study aimed at determining the four major groups of antioxidants (flavonoids, phenolic acids and aldehydes, catechin and procyanidin) in rootstocks of Crataegus laevigata (genotypes O-LE-14 and O-LE-21), Aronia melanocarpa (genotypes O-LE-14 and O-LE-21), Chaenomeles japonica (genotype O-LE-9) and Cydonia oblonga (BA 29) (genotypes O-LE-14 and O-LE-21). Hyperoside (Quercetin 3-D-galactoside) was the most abundant flavonoid compound, since its average content in the rootstocks of Crataegus laevigata (O-LE-21) was 180.68 ± 0.04 μg·g-1. Dihydrokaempherol was the least frequently found flavonoid compound, with an average concentration of 0.43 ± 0.01 μg·g-1 in all the rootstocks of plants considered in this study. Among the phenolic compounds, the most represented one was protocatechuic acid, with 955.92 ± 10.25 μg·g-1 in the rootstocks of Aronia melanocarpa (O-LE-14). On the other hand, the least represented p-Coumaric acid exhibited the average concentration of 0.34 ± 0.01 μg·g-1 in the plant rootstocks. Epicatechin was the most abundant catechin compound, with a content of 3196.37 ± 50.10 μg·g-1 in the rootstocks of Aronia melanocarpa (O-LE-14). The lowest represented catechin compound was epigallocatechin, with the average concentration of 0.95 ± 0.08 μg·g-1 in the screened plant rootstocks. From the procyanidin compounds, the most abundant one was procyanidin b2 in the rootstocks of Crataegus laevigata (O-LE-14), with a concentration of 5550.40 ± 99.56 μg·g-1. On the contrary, procyanidin a2, with an average concentration of 40.35 ± 1.61 μg·g-1, represented the least frequent procyanidin compound in all the plant rootstocks screened herein.
Keywords: Sorbus domestica; flavonoid compounds; rootstocks of plants; phenolic compounds; LC/MS; catechin compounds; procyanidin compounds